Rational Finance for Sustainable Development "Financial Plans by Omar Bin Abdulaziz- A model" - Houbad, Ahmed Tayeb (Journal of Humanities & Social Sciences, 2021)
There is no doubt that the successful public finances are the ones which achieve development that accommodate all the economic, social, political and other dimensions. This is what the Omar’s fiscal policy was able to do in a short time, and in an unprecedented way This policy has inherited a deteriorating financial system due to the fact that many excesses and irregularities were caused by the successors of the Bani Umayyad before him. This in turn caused political unrest and social divisions that led to a deficit in the fiscal budget. The researcher concluded that Caliph Omar bin Abdulaziz was able to get rid of the budget deficit through plans he adopted in the aspect of revenues and expenditures, which were generally represented in adherence to the legislation contained therein, providing flexible facilities and plans to manage them, and working to expand the circle of social spending and eliminate cases of administrative corruption. The researcher recommends conducting research to study age- based financial plans to avoid economic inflation, as well as specialized research to establish departments for financial revenues that governments have abandoned today, such as zakat and tax)kharaj)